Le temps d’un thé : À la rencontre des familles fondatrices - Centre for Access to Services in English (CASE) (2023)

Remembering Drummondville’s First Families : A Very Special Heritage Tea and Talk - Centre for Access to Services in English (CASE) (2023)

Partners in Health - Centre for Access to Services in English (CASE) (2023)
Number of pages: 4

Blue Skies : An Evening of Jazz and R&B - Centre for Access to Services in English (CASE) (2023)

Partners in Health - Centre for Access to Services in English (CASE) (2022)
Number of pages: 3

Concert de Noël : Chants et souvenirs de Noël - Centre for Access to Services in English (CASE) (2022)
Parallel title: Christmas Concert: Carols and Christmas Memories

Partners in Health - Centre for Access to Services in English (CASE) (2022)
Number of pages: 4

Récits d’un petit “shtetl” : histoire de la communauté juive de Drummondville - Miller, Julie (2022)

Stories of a Small “Shtetl” : Jewish History in Drummondville - Miller, Julie (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)
Number of pages: 4

Money Raised for La Rose des Vents de Drummond and a Successful First Edition of the “History and Music” Concert Series - Centre for Access to Services in English (CASE) (2022)

Concert Series to Highlight Talents of Young Musicians Celebrating Local Heritage in the Sonorous Acoustics of St George Anglican Church - Centre for Access to Services in English (CASE) (2022)

"Carols and Christmas Memories" : A Holiday Community Concert Featuring Familiar Tunes and Personal Tales of Christmases Past - Centre for Access to Services in English (CASE) (2021)

Hats and High Tea : Local Collector to Share "Mobile Museum" in Bilingual Talk Highlighting the History of Fashion from 1940-1965, Followed by a Traditional English-style High Tea - Centre for Access to Services in English (CASE) (2021)

Peer-reviewed by Fifth-graders : International Science Journal Brings Drummondville Students to the Frontier of Cutting Edge Discoveries - Centre for Access to Services in English (CASE) (2021)

Over 450 Years of Song: Religious Heritage Days Concert - Centre for Access to Services in English (CASE) (2021)

Window Onto Local Farming : Être femme en agriculture / Women in Agriculture - Miller, Julie; Lapierre, Carole-Anne (2021)

Raise a Glass to the Season! : CASE-MCQ Invites You to an Evening of Stories, Music and Conversation with Rob Lutes - Centre for Access to Services in English (CASE) (2020)

$40,000 Awarded in Student Leadership Bursaries for the Mauricie/Centre-du-Québec Region - Miller, Julie; Vidal, Emily (2020)

Fall Colours Acoustic Concert - Cancelled Due to COVID-19 - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)
Number of pages: 3

Partners in Health - Centre for Access to Services in English (CASE) (2019)
Number of pages: 3

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Drummond (0417) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Invitation aux media : Conférence de presse - Centre for Access to Services in English (CASE) (2016)